Identification of six Listeria species by real‐time PCR assay. (24th February 2014) - Hage, E.; Mpamugo, O.; Ohai, C.; Sapkota, S.; Swift, C.; Wooldridge, D.; Amar, C.F.L.
Abstract The Listeria genus comprises 10 recognized species. Listeria monocytogenes causes listeriosis in humans and other animals primarily via contaminated food or animal feed. Listeria ivanovii causes listeriosis in animals and on rare occasions in humans. The identification of nonpathogenic species of Listeria in foods indicates that conditions exist that support the growth of pathogenic strains and is used to facilitate the implementation of control and prevention measures. This study shows the development and evaluation of a 5′exonuclease real‐time PCR assay for the rapid identification of Listeria seeligeri, Listeria welshimeri, L. monocytogenes, L. ivanovii, Listeria grayi and Listeria innocua. The assay consists of two triplexes that were evaluated using 53 cultures of Gram‐positive bacteria, including 49 Listeria spp. from human, animal, food or food‐processing environments. The assay was rapid, specific and reproducible and could identify each of the six species from a mixture of strains. The developed assay proved to be a powerful means of rapidly identifying Listeria species and could be usefully implemented in busy specialist reference laboratories. Significance and Impact of the Study The identification of species of Listeria from foods is important to monitor pathogenic strains and facilitates the implementation of control measures. This study shows the development and evaluation of a 5′exonuclease real‐time PCR assay for the rapid identification of L. seeligeri, L. welshimeri, L. monocytogenes and L. ivanovii, L. grayi, L. innocua. The developed assay proved to be specific, rapid and reproducible and therefore could be implemented in busy specialist reference laboratories.